Incidence of MRI-detected brain lesions and neurocognitive function after electrical cardioversion in anticoagulated patients with persistent atrial fibrillation. (15th September 2017) - Bellmann, B.; Fiebach, J.B.; Guttmann, S.; Lin, T.; Haeusler, K.G.; Bathe-Peters, R.; Koehler, L.; Steffens, D.; Kasner, M.; Tscholl, V.; Nagel, P.; Roser, M.; et al.
Abstract: Background: After electrical cardioversion (eCV) in patients with atrial fibrillation (AF), the risk for clinically apparent cerebral thromboembolism is increased in the subsequent weeks. To date, there is little evidence on the incidence of acute brain lesions (ABL) detected with cerebral magnetic resonance imaging (MRI) after eCV, in particular in patients treated with the Non-Vitamin K Antagonist oral anticoagulants (NOAC). Aims: The aim of this pilot study was to evaluate the incidence of MRI-detected ABL, as well as the neuro-cognitive function after eCV in patients with persistent AF using NOACs as compared to phenprocoumon. Methods and results: 50 consecutive patients with persistent AF (mean age 69.6 ± 3.5 years, 26 male) were evaluated in this prospective study. Cerebral 3 Tesla MRI and neuro-cognitive assessment using the National Institutes of Health Stroke Scale (NIHSS) score and the Montreal Cognitive Assessment Test (MoCA) were performed in all patients within 24 h before eCV and after a median follow-up duration of 14 days (Q1: 13, Q3: 19 days). Patients were treated with an OAC for at least 4 weeks after eCV and according to the CHA2 DS2 -Vasc-score thereafter. Thirty-nine patients were treated with NOACs (Dabigatran 10/50 [20%], Apixaban 21/50 [42%] and Rivaroxaban 8/50 [16]) and 11/50 patients with Phenprocoumon (22%). No patient developed ABL on cerebral MRI at the 2-week follow-up. Neurological as well as cognitive function were similar before and 2 weeks after eCV (NIHSS-score: p = 0.35; MoCa score: p = 0.21). Conclusion: Electrical CV in patients with persistent AF, in particular when treated with NOACs, carries a low risk for the development of MRI-detected ABL or neurocognitive decline. Clinical trials registration: GermanClinicalTrialsRegister number: DRKS00010460. Highlights: Electrical cardioversion in patients with novel oral anticoagulants, carries a low risk for MRI-detected acute brain lesions. No acute brain lesions in the study population were detected even when using 3 Tesla MRI. No significant impact on neurocognitive function was observed after electrical cardioversion in this study population.